Defoliation Dynamics on Grazing Horizons in Pastures Intercropped by Panicum maximum, Brachiaria brizantha, and Brachiaria decumbens - P. B. Fernandes; R. A. Barbosa; M. G. Morais; C. Medeiros-Neto; A. F. Sbrissia; H. J. Fernandes; G. S. Difante (Faculty of Animal Science, Bogor Agricultural University, 2020)
The aim of this study was to quantify and verify the defoliation dynamics process of the Panicum maximum, Brachiaria brizantha, and Brachiaria decumbens intercropping during the formation of four grazing horizons in lenient grazing intensities and high grazing intensity. Pastures were managed in a pregrazing height of 70 cm, and as post-grazing height, the criteria of 40% and 60% were used in relation to the pre-grazing height. The experimental design used was a completely randomized design with a 3x4 factorial arrangement. The first factor was the cultivars of intercropped grasses consisted of 3 cultivars, i.e., BRS Zuri, Xaraés, and Basilisk. The second factor was grazing horizons consisted of 4 levels, i.e., I: one; II: two; III: three; IV: four. In the intercropping managed with 40% of the forage canopy height removal, oscillations were observed in the severity of defoliation of the extended tiller among the intercropped species, in which the tiller reduction of the ‘Basilisk’ was 32% lower in relation to ‘BRS Zuri’. In the intercropping managed with 60% of the forage canopy height removal intensity, disproportionality was observed among the grasses, because the ‘Basilisk’ suffered a higher severity and frequency of pseudostem defoliation. In intercropped pastures managed under grazing intensities of 40%, as the animal explores the grazing horizons, the vertical distribution of the pseudostem could modify the shape and positioning of the depth of the bite, leading the animal to perform less selective grazing among the species. Due to the higher supply of pseudostem mass at the intensity of 60%, it was possible to infer that there was a reduction in forage intake.